WAYS FOR REDUCING OVERWEIGHT AND OBESITY IN CHRONIC LIVER DISEASES - Djumaev B.Z. (Galaxy International Interdisciplinary Research Journal, 2022)
The Bukhara Regional Multidisciplinary Clinical Medical Center studied 98 patients with chronic liver disease, overweight and obesity who were treated in a hospital setting. Excess body weight and obesity in chronic liver disease have benefited from Ibn Sina’s health interventions in practice. Slightly more ADRB3 (rs4994) Trp 64 Arg gene 2 genotypes in patients with primary chronic liver disease overweight and obesity Trp / Trp 55%, Trp / Arg in 45% of cases, ADRB2 in patients with secondary chronic liver disease overweight and obesity (rs1042713) The A> G, AG genotype occurred in 62.5% of cases and the Trp / Trp genotype in the highest 75% of cases. In patients diagnosed with overweight and obesity in tertiary chronic liver disease, the C / C genotype of the PPARG2 (rs1801282) gene was reported to be at most 68.7% of cases, while the G / G genotype was almost undetectable.